Change Labor Force Structure in Indonesia: An Overview Demographic and Economic Literature - Saputra, Ahmad Redo; Rizqullah, Muhammad Nabil (International Journal of Economic, Business & Applications, 2025)
This study aims to analyze the structural changes in the Indonesian workforce using an approach that integrates demographic and economic perspectives. The primary objective of this study is to explore the dynamics of the workforce composition stratified by age, gender, education, and economic sector, and their impact on national development policies and sustainable economic growth. These structural changes are examined within theframeworkof demographic transition, urbanization, economic globalization, and technological advances, which simultaneously influence labor supply and demand. The techniques used  a systematic literature review of scientific publications, policy reports, and official secondary data from various national institutions over the past two decades. The analized references were selected based on their thematic relevance, empirical validity, and contribution to explaining changes in the structure of the Indonesian workforce. The analysis method was thematic and descriptive-critical to capture patterns of change, key challenges, and emerging strategic opportunities. The analysis shows that Indonesia is currently experiencing a demographic bonus, marked by an increasing number of individuals in the productive age group. However, this potential has not been fully utilized due to low female participation rates in the workforce, a skills gap, and structural inequalities between the formal and informal sectors. Furthermore, a significant shift from the primary to the tertiary sector has been observed, but this has not been accompanied by improvements in job quality. This study recommends strengthening employment policies, investing in vocational education, and restructuring the labor market to support an inclusive and sustainable economic transformation.